Repulsion [videorecording (DVD)] - Polanski, Roman; Polanski, Roman; Deneuve, Catherine, 1943-; Furneaux, Yvonne, 1928-; Hendry, Ian, 1931-1984 (Criterion collection, 2009)
Carol is a fragile, frigid young Belgian beauty cracking up over the course of a terrifying weekend. Left alone by her vacationing sister in their London flat, she finds herself haunted by specters, real and imagined, as her insanity grows to a violent pitch.